Chinese Tourists in Hotel Industry - Rozsypálková, Jessica; Abrhám, Josef; Hasík, Gabriel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The goal of the Master Thesis is to analyze behavior of Chinese tourist in hotel industry. The analysis is based on questionnaires of three Chinese professionals who worked in a Chinese hotel, three foreigners (Russian, Italian, Spanish) who as well worked in a Chinese hotel and three Czech professionals who worked in a Czech hotel frequently visited by Chinese tourists. The thesis subsequently introduces ways how Chinese tourists should be treated during their visit in a hotel with respect to their origin and culture. The main aim of the first chapter is to describe behavior of Chinese people with all their specifics. Second chapter focuses on the growing middle class in China which enormously influences the outbound tourism. Third chapter determines inbound as well as outbound tourism in China and its history. Furthermore, the developing hotel industry in China is introduced. Finally, the fourth chapter is the research part where cultural specifics of Chinese travelers are analyzed. The last chapter provides recommendations to hotels who are accommodating Chinese tourists.
Vedoucí práce: Josef Abrhám
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses